Mainstreaming climate change in policy frameworks for community-based natural resource management in a semi-arid savannah environment: case study of Botswana - Oliver Chikuta; Olga L. Kupika; Olivia Nthoi (Frontiers in Sustainable Tourism, 2024)
Community-based natural resource management (CBNRM) is a concept that was introduced in southern Africa back in the 1980s with the dual aim of biodiversity conservation and poverty reduction in communities endowed with natural resources. Community-based tourism (CBT), one of the major forms of CBNRM, depends on natural resources, particularly wildlife, and weather and climatic conditions. However, natural resources are under threat from climatic changes and other anthropogenic and natural disturbances. This calls for the need to interrogate the extent to which CBNRM initiatives mainstream climate change in their agenda. The main aim of this article is to assess the extent to which the climate change agenda has been mainstreamed into the policy framework of Botswana's CBNRM program. The specific objectives are to (1) document the impacts of climate change on CBNRM-related initiatives in Botswana; (2) determine the relationship between climate parameters (temperature and rainfall), extreme events (drought and extreme heat), and visitor trends in Botswana and the Okavango Delta; (3) establish a historical correlation between evolution of climate change policy and CBNRM policy and vice versa, policy initiatives, programs, strategies, and projects in Botswana; (4) explore the extent to which international, regional, national, and local climate policies mainstream CBNRM and tourism issues and vice versa; and (5) explore the challenges and opportunities related to climate change and CBNRM, with a particular focus on adaptation and mitigation initiatives. This study mostly used qualitative approaches (desktop review of policy documents and scholarly articles) as well as secondary quantitative data (time-series data) to explore the evolution of CBNRM in Botswana, providing an overview of its structure, policy initiatives, programs, and projects and how these correspond with climate change issues. A scoping review was conducted to identify relevant studies on the impacts of climate change on CBNRM initiatives published between 1992 and 2023. A total of 50 articles were identified to answer the following research question: What evidence is available regarding the impacts of climate change on CBNRM initiatives? The article further looks at how climate change–related extreme events, particularly drought, has affected tourism performance over the years. The article then zeros down on the effects of climate change on CBNRM initiatives and the challenges, threats, and opportunities, as well as the mitigation and adaptation strategies adopted by the CBNRM projects in Botswana. The findings indicate that climate change–induced events, particularly drought, have affected nature-based tourism products in Botswana. However, it was revealed that although there is no statistically significant correlation between drought and tourism performance, evidence from the literature reveals that drought has impacted tourism in Botswana. The findings from policy analysis indicate that the climate change agenda is woven into more recent key legal and policy documents on CBNRM, on one hand, while the climate change policy documents also include components that speak to CBNRM, on the other. This implies that the tourism sector can leverage these provisions to strengthen climate resilience through transformative adaptation and mitigation action.